2008
DOI: 10.1093/eurheartj/ehn138
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged statin-associated reduction in neutrophil reactive oxygen species and angiotensin II type 1 receptor expression: 1-year follow-up

Abstract: A consistent reversion of pro-inflammatory oxidative functional response and reduction of AT(1)-R expression in primed PMNs was observed in patients during long-term statin treatment. The AT1-R reduction over treatment may contribute to the normalization of dysregulated neutrophil activation which occurs in the pre-clinical phase of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
1
36
1
Order By: Relevance
“…Investigations of the several leucocytic transcripts noticeably elevated in CKD patients revealed that only the receptor for AngII, AT1R was positively correlated with an increased miR-421 expression. It has been reported that AT1R expression on leukocytes may be modulated by pharmacological intervention [32] or affected by the uremic factors [33]. However, based on our data, we can speculate only that AT1R expression could be indirectly regulated by miR-421, since it does not contain any binding site for this miR (http://www.mirdb.org).…”
Section: Discussionmentioning
confidence: 64%
“…Investigations of the several leucocytic transcripts noticeably elevated in CKD patients revealed that only the receptor for AngII, AT1R was positively correlated with an increased miR-421 expression. It has been reported that AT1R expression on leukocytes may be modulated by pharmacological intervention [32] or affected by the uremic factors [33]. However, based on our data, we can speculate only that AT1R expression could be indirectly regulated by miR-421, since it does not contain any binding site for this miR (http://www.mirdb.org).…”
Section: Discussionmentioning
confidence: 64%
“…Of particular interest, a low-grade systemic inflammatory condition usually occurs in asymptomatic people who nonetheless bear one or more risk factors for the development of cardiovascular disease (high risk subjects according to the National Cholesterol Education ProgramAdult Treatment Panel III (ATPIII) guidelines [30]). Such condition includes activation of circulating PMNs with increased production of ROS and secretion of IL-8 [31,32], and provide substantial contribution to the vascular damage which finally results in the formation of atherosclerotic plaques. At present, it is well established that early treatment with antidysplipidemic/antiinflammatory drugs such as statins effectively reverses such immune activation [31,32], nonetheless attainment of the same therapeutic target by use of dietary strategies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well known that isolated traditional CRF and clustered high cardiovascular risk conditions are associated with inflammation both expressed as increased systemic markers and pro-inflammatory cellular responses [19][20][21][22][23][24][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In our patients burdened by major CRF and poly-treated, the greater prevalence of obesity in OSA group did not result in increased cytokine cellular production from both PBMCs and PMNs or in increased serum levels of the investigated cytokines. Since it has been reported that pro-inflammatory changes in various cell types are affected by the risk profile of the subjects [16][17][18][19][20][21][22][23][24] it is likely that these CRF may constitute major confounding issues in studies associating OSA with inflammation. Moreover, it has been reported that drugs used in counteracting major CRF such as statins, calcium-channel blockers, and angiotensin-converting enzyme inhibitors can reduce the upregulated pro-inflammatory cellular responses [16][17][18][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation